Disinterment & its Medico-legal Significance in Karachi (Medical Forum Monthly, 2020)
Objective: To study different aspects of Exhumation which were conducted and autopsied in Karachi City.Study Design: Retrospective study.Place and Duration of Study: This study was conducted at the Departments of Forensic Medicine / Pathology, KMDC, Karachi and Liaquat College of Medicine & Dentistry, Karachi from January 2017 to December 2018.Materials and Methods: Thirty-nine cases of exhumation were included which were overseen in two years study period. The data was collected with the permission of authorities. All the cases where cause of death was determined and other with undetermined cause of death were included in the study. Different variables e.g. age, sex, type of examination, manner of death, cause of death, time of burial and disinterment and condition of body were analyzed using SPSS Version 13.Results: A total of 39 Exhumation were carried out during the study period of two years. Out of the total 20 were males (51.28%) and 19 females (48.71%), giving a male to female ratio of 1:0.95. In about 30 cases cause of death was established with certainty. Most frequent un-natural cause of death is asphyxia (46.15%) followed by hard and blunt trauma (10.25%), electrocution (7.69%), firearms (5.12%), sharp cutting-edge injury (2.56%), and poisoning (2.56%) respectively.Conclusion: There is a need of DNA labs setup in different major cities so that the cases, especially for the identification purpose, will be declared and the results be seen on shortest possible time.